FUNCTIONAL STATUS AND ACTIVITIES OF DAILY LIVING IN PATIENTS WITH OSTEOPOROTIC VERTEBRAL COMPRESSION FRACTURES AT THE SPINE CLINIC, MILITARY CENTRAL HOSPITAL 108, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the functional status and activities of daily living in patients with osteoporotic vertebral compression fractures at the Spine Clinic, Military Central Hospital 108 in 2025.Methods: A cross-sectional descriptive study enrolled 200 osteoporotic vertebral compression fractures patients (T-score ≤ -2.5) from January to August 2025. Basic activities of daily living were assessed using the Barthel Index and instrumental activities of daily living (IADL) using the Lawton IADL scale.Results: Mean age was 69.97 ± 8.11 years; 92% were female. Mean Barthel Index score was 82.63 ± 16.95; 80.5% of patients had varying degrees of dependency, with moderate dependence being most common (53.5%). The most impaired activities were transferring (77.5%), stair climbing (66.5%), and walking on flat surfaces (52%). Mean Lawton IADL score was 5.85 ± 2.07; 66% had some degree of impairment in instrumental activities. The most affected activities were housekeeping (69%), transportation (68%), and laundry (67.5%).Conclusion: Osteoporotic vertebral compression fractures patients experience significant impairment in both basic and instrumental activities of daily living, highlighting the need for systematic functional assessment in nursing and rehabilitation practice.
Keywords: Vertebral compression fracture, osteoporosis, Barthel Index, Lawton IADL, activities of daily living.